Ultrahigh sensitive graphene oxide/conducting polymer composite based biosensor for cholesterol and bilirubin detection - Kumar, Anup; Gupta, Gourang Hari; Singh, Gajendar; More, Namdev; M, Keerthana; Sharma, Ashish; Jawade, Dhanajay; Balu, Aishwarya; Kapusetti, Govinda (Biosensors and bioelectronics. X, 2023)
Methods for detecting life-threatening diseases like cardiac arrest and arrhythmias are urgently required that are affordable and selective. The creation of nanocomposite based on graphene oxide, zinc oxide, polypyrrole, and polyaniline is one embodiment of the current disclosure. The nanocomposite of the present invention has highly enhanced the detection sensitivity of cholesterol and bilirubin. The dispersion of components in 1 (M) sulphuric acid is used to generate nanocomposite using the direct mixing technique. Glassy carbon electrodes are employed as the substrate material in the fabrication of nanocomposite-based biosensors. The sensor has demonstrated sensitivity of 0.92 μA μM−1 cm−2 and 0.2 μA μM−1 cm−2 for the detection of cholesterol and bilirubin, respectively. The innovative technology has enhanced lower detection limits, lower quantification limits, and good selectivity, among other things. In comparison to existing reports, the developed sensor has demonstrated greater sensitivity for the detection of cholesterol and bilirubin. As a result, the composite platform is ideal for the creation of high-sensitivity biosensors for a wide range of biomarkers. [Display omitted] •The GO/PPy/PANI/ZnO nanocomposite was first tested for cholesterol and bilirubin detection.•The nanocomposite displayed improved porosity and better electron transmission.•Developed electrode showed a enhanced electrical conductivity.•The sensor demonstrated substantially higher sensitivity for cholesterol and bilirubin detection .•The sensor demonstrated a remarkable detection limit, linearity and selectivity.